Perancangan Taman Kreativitas Pemuda di Kabupaten Tegal Dengan Pendekatan Arsitektur - Achmad Nur Iskhaq; Inggit Musdinar Sayekti Sihing Yang Mawantu; Harfa Iskandaria (MAESTRO, 2023)
A creative community is an association that is formed because of similar hobbies and interests that are creative in nature. Indonesia is currently experiencing significant development, one of which is in the Tegal Regency area. Tegal Regency is one of the regencies in Central Java with the capital city of Slawi City. There are many creative community and creative economy actors in Tegal Regency in the field of arts and creative industries that require facilities to support their activities and are supported by the local government. This potential is one of the drivers to create and build in the regional economic sector. The Youth Creativity Park is a building area that aims to accommodate the activities of the creative community and creative industries in Tegal Regency. Through the ecological architectural approach in the design of the Youth Creativity Park, it is expected to increase the creativity of creative community actors and creative economic actors who are expected to be able to accommodate and facilitate the activities of the creative community to build a creative economy in the region and provide a balanced impact of change on buildings, the environment and respond to climate conditions against changes that occur due to the warming of the earth created through the mass of the building and the space inside with the behavior of processing natural resources.